2018
DOI: 10.1108/jarhe-08-2017-0103
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders’ roles in field experience: some empirical evidence

Abstract: Purpose Field experience (FE) has long been a crucial component of the process of teacher education. Clearly, a range of stakeholders can affect student-teachers’ achievements in FE. Given the importance of these stakeholders in FE, it may be possible to improve FE practices by clarifying the involvement of different parties in the FE process. Since student-teachers are the major beneficiaries in FE, their voices should not be ignored. Therefore, the purpose of this paper is to explore student-teachers’ percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…However, it has been argued in previous studies that HEIs tend to be conservative especially in terms of teaching methods, assessment and research [52]. There is a tendency for some academics to rely on old teaching and research methods using materials that are never updated [54,56] as well as failure to manage online teaching [47,8]. Thus, academic freedom inspired by institutional vision and mission may not suffice in using the available knowledge to design quality assurance mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been argued in previous studies that HEIs tend to be conservative especially in terms of teaching methods, assessment and research [52]. There is a tendency for some academics to rely on old teaching and research methods using materials that are never updated [54,56] as well as failure to manage online teaching [47,8]. Thus, academic freedom inspired by institutional vision and mission may not suffice in using the available knowledge to design quality assurance mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed that knowledge management is crucial in enabling institutions gain and maintain a competitive advantage [43]. Higher Education Institutions (HEIs) especially universities are popularly known for knowledge generation through teaching and research [7,40,48,54]. Yet, HEIs continue to grapple with internal quality assurance challenges amidst knowledge accumulation through research and practice [1,15,16,58].…”
Section: Introductionmentioning
confidence: 99%